Pengaruh Rutinitas Membaca Asmaul Husna Terhadap Emotional Intelligence Pada Anak usia 5-6 Tahun - Siti Sarofa; Amirul Mukminin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to investigate the influence of the routine recitation of Asmaul Husna on the development of emotional intelligence in early childhood students at TK Janneta. The recitation of Asmaul Husna is considered a form of spiritual habituation that is believed to support children's ability to recognize, understand, and manage their emotions. A quantitative approach was employed, using simple linear regression analysis to examine the data. The participants consisted of Group B students at TK Janneta who regularly engaged in the Asmaul Husna recitation activities conducted at school. The findings revealed a significant positive effect of the routine recitation on emotional intelligence, contributing 22.4% to the variance in emotional intelligence levels. These results suggest that incorporating spiritual practices such as the recitation of Asmaul Husna can play a meaningful role in enhancing children's emotional development, particularly in their capacity to identify, comprehend, and regulate emotions effectively.